Implementasi Guided Walking Imagery Berbasis Audio Terhadap Tingkat Stres Pada Mahasiswa Keperawatan Dalam Menghadapi Penyusunan Tugas Akhir - Hanan, Cholid Tri Ananta; Muhammad Al-amin; Yulifah Salistia Budi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: The final project is one of the main factors contributing to stress among final-year students. The pressure intensifies due to challenges such as limited time, restricted access to data, and repeated revisions. One non-pharmacological solution that can be applied to reduce stress is Guided Walking Imagery Audio, a relaxation technique based on audio guidance that helps calm the mind through guided visualization. Objective: This study aims to determine the effect of implementing Guided Walking Imagery Audio on stress levels among nursing students in completing their final projects. Methods: The study employed a pre-experimental design with a one-group pre-test and post-test approach, using total sampling on 19 final-year students of the Diploma III Nursing Program. Data were collected using the PSS-10 questionnaire, with the Guided Walking Imagery Audio intervention administered over five days, 15 minutes per session. Results: Data analysis using the Paired Sample T-Test showed a p-value of 0.000 (p < 0.05), indicating that this intervention effectively reduced students’ stress levels. Conclusion: Guided Walking Imagery Audio can be considered a practical and easily applicable solution to help students manage stress during the final project process.